Emotional profile of mathematics teachers - García-González, María S. (2020)
This research explores the impact of negative emotions of 2 teachers at the moment they are teaching mathematics through an emotional profile. The methodology adheres to the qualitative paradigm, and the research design is the case study. The participants are Karla, a novice high school teacher (15-18-year-old students) and Norma, an experienced primary school teacher (6-12-year-old students). The results demonstrate that Karla experiences 5 emotions during the teaching of mathematics, 2 positive (joy and pride) and 3 negatives (self-reproach, reproach, and distress). Norma has 5 emotions, 2 positive (joy and satisfaction) and 3 negatives (self-reproach, disappointment, and remorse). In the case of Karla, her negative emotions lead her to lose her motivation, when she is teaching; in a certain way, she tends to avoid classroom situations that trigger those negative emotions. In Norma’s case, negative emotions are related to her poor mathematical knowledge, therefore she feels “unarmed” to be able to face the demands of her students when she experiences negative emotions; unlike Karla, Norma faces the situations that trigger in it the negative emotions. Based on the analyzed cases, we emphasize the importance to develop the emotional knowledge in math teachers to optimize the regulation of the negative emotions and develop their classes in an emotionally stable environment.